Pathogenesis of Trousseau’s syndrome - A. V. Vorobev; A. M. Chabrov; A. A. MD, Ph.D., head of gynecological department; S. V. Bulgakova; A. D. Makatsariya (Акушерство, гинекология и репродукция, 2016)
After the first observations A. Trousseau in 1865, it is exist a host of studies on the relationship between the pathogenesis of cancer and thrombosis. There is now no doubt that the cancer patients occur much more frequently thromboembolism, and migratory venous thrombosis is a manifestation of paraneoplastic syndrome in cancer patients. In general, any manifestation of thrombohemorrhagic complications in cancer patients called Trousseau’s syndrome. While thrombotic complications such as venous thromboembolism are most frequent in cancer patients, may also experience severe bleeding symptoms due to systemic coagulopathies, including disseminated intravascular coagulation, haemolytic thrombotic microangiopathy, and hyperfibrinolysis. The basis of the pathophysiology of Trousseau’s syndrome, except the classic triad of Virchow, is overproduction of tissue factor, the main initiator of extrinsic coagulation pathway. Thus a significant release of microparticles from tumor cells bearing tissue factor is critical not only for the formation of a blood clot, but the growth and progression of tumors. Tumor cells activate the coagulation cascade or fibrinolysis system, providing conditions for its further spread, stimulation of angiogenesis, increased vascular permeability, which in turn promotes metastasis